Coordinating gallium hexacyanocobaltate: Prussian blue-based nanomaterial for Li-ion storage - Zhang, Kaiqiang; Lee, Tae Hyung; Bubach, Bailey; Ostadhassan, Mehdi; Jang, Ho Won; Choi, Ji-Won; Shokouhimehr, Mohammadreza (ROYAL SOC CHEMISTRY, 2019)
Prussian blue analogs (PBAs) are a type of metal-organic framework and have drawn significant attention recently. To date, most are constructed with divalent transition metal ions coordinated to the N end of a cyanide bridge. In this report, we studied a trivalent gallium ion-based Ga hexacyanocobaltate (GaHCCo), which depicted a face-centered cubic crystal structure. In addition, the synthesized GaHCCo was demonstrated as a cathode material of lithium-ion batteries (LIBs) and was found to exhibit long-term stability, having a capacity retention of 75% after 3000 cycles of repeated charge-discharge cycling and an extremely high coulombic efficiency of 98%, which was achieved because of a solid-state diffusion controlled Li-ion storage process. After ex situ XRD analysis on the different charge stages, the Li-ion storage in the GaHCCo was attributed to the Co species via the formation of a Li/Co compound. This work will pave the way toward the study of PBAs constructed with trivalent metal ions and provide more insights into the development of high-performance LIBs in the future.
Keywords: HEXACYANOFERRATE NANOPARTICLES; IRON HEXACYANOFERRATE; CATHODE MATERIALS; LITHIUM; ANALOG; CATALYSTS